Penegakan Hukum Tindak Pidana Kehutanan Berdasarkan Undang-Undang Pencegahan dan Pemberantasan Perusakan Hutan - Putri Regina Fadillah Natasya; Suwari Akhmaddhian (Universitas Kuningan, 2025)
This article discusses forestry crimes, specifically the prevention and eradication of forest destruction, with a focus on Decision Letter Number 454/Pid.B/LH/2023/PN Spt. The purpose of this paper is to identify the types of forestry crimes and analyze dispute resolution mechanisms based on these cases. The method used is normative legal research, involving the review and analysis of applicable laws and regulations and legal practices. The results show that forestry crimes, such as illegal logging and document falsification, are regulated by Law Number 18 of 2013. The case analyzed illustrates how invalid forest product certificates can result in strict criminal sanctions. The High Court upheld the previous decision, demonstrating that the legal system functions to uphold justice. In conclusion, preventing forestry crimes requires a holistic approach involving strict law enforcement, community empowerment, and inter-agency collaboration. Success in eradicating forest destruction will depend on public legal awareness and firm enforcement.